Jack Ryan : The Sum Of All Fears - Book 5 - Clancy, Tom, 1947-2013. (New York, 1992)
One terrible act plunges the world into an instant nuclear crisis, and with the American president accused of incompetence, Jack Ryan calls on FBI head Dan Murray to help him avert disaster.
Berkley mass market edition, August 1992--T.p. verso.
Keywords: Ryan, Jack, Sr. (Fictitious character) -- Fiction; Intelligence service -- United States; Fiction; Nuclear warfare -- Fiction; Adventure fiction; Spy stories